STRUKTUR KEPEMILIKAN SEBAGAI MEKANISME PENINGKATAN KUALITAS AUDIT DAN DAMPAKNYA TERHADAP REAKSI PASAR - Stevi Wijaya; Suwandi Ng; James Raynold Gandasully (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2019)
The purpose of this research was to investigate whether foreign ownership and government ownership have an impact on audit quality and whether audit quality has an impact on market reaction. The population used in this research are all companies listed on the Indonesia Stock Exchange with the research period 2015-2017. The method of determining the sample using purposive sampling with certain criteria and using secondary data so that only 102 companies were selected to used being sample, The method of analysis used linear regression analysis using SPSS 20. The results of this research show that foreign ownership has a positive but not significant impact on audit quality. Government ownership has a positive and significant impact on audit quality. While audit quality has a positive and significant impact on market reaction. The implication is foreign and government ownership are expected to use Public Accounting Firm with good competence and experience capable of evaluating and verifying financial statements so thai it is free from mistakes that will improve the credibility of financial statements, and increasing the confidance of users of financial statements such as shareholders,creditors. So it will affect the company stock price.